2017
DOI: 10.1186/s40104-016-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus subtilis CSL2 on the composition and functional diversity of the faecal microbiota of broiler chickens challenged with Salmonella Gallinarum

Abstract: BackgroundThe chicken gastrointestinal tract contains a diverse microbiota whose composition and structure play important roles in gut functionality. In this study, microbial shifts resulting from feed supplementation with Bacillus subtilis CSL2 were evaluated in broilers challenged and unchallenged with Salmonella Gallinarum. To analyse bacterial community composition and functionality, 454 GS-FLX pyrosequencing of 16S rRNA gene amplicons was performed.ResultsThe Quantitative Insights into Microbial Ecology (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(128 citation statements)
references
References 29 publications
9
113
3
Order By: Relevance
“…After quality control, 228 samples were retained and we obtained 4,995,664 sequences with a total of 3,993 amplicon sequence variants (ASVs). The frequency of reads per sample varied from 3,527 to 210,082 with an average of 21,911 and a median of 18,130 per sample, which is comparable to previous studies [46,47].…”
Section: Sequencing Informationsupporting
confidence: 83%
“…After quality control, 228 samples were retained and we obtained 4,995,664 sequences with a total of 3,993 amplicon sequence variants (ASVs). The frequency of reads per sample varied from 3,527 to 210,082 with an average of 21,911 and a median of 18,130 per sample, which is comparable to previous studies [46,47].…”
Section: Sequencing Informationsupporting
confidence: 83%
“…Nevertheless, stress conditions or GIT pathogen colonization can induce a reduction of microbial diversity in poultry [20,21]. The loss in diversity driven by a dysbiotic microbiota is found with a carriage of commensals such as lactobacilli reduced, while the level of Enterobacteriaceae increased [22,23]. Here, in this study, there was no pathogen challenge or evident environmental stress imposed on the broilers during the experimental period.…”
Section: Discussionmentioning
confidence: 95%
“…Changes in sperm fatty acids composition was shown to occur during epididymal maturation through the incorporation of lipids from the organ microenvironment (Parks & Hammerstedt 1985, Hall et al 1991, Aveldaño et al 1992, Haidl & Opper 1997, Pyttel et al 2014, Angrimani et al 2017. Our measures in C. perspicillata confirmed that a change in the PUFA composition occurred during the passage from the caput to the cauda epididymidis, with a partial replacement of the n-6 PUFAs by the n-3 PUFAs, without any significant change in the overall PUFA proportion.…”
Section: Discussionmentioning
confidence: 99%
“…In most species studied so far, mature sperm cells from the cauda epididymidis comprise a higher proportion of polyunsaturated fatty acids (PUFAs), and especially of n-3 PUFAs (also referred to as omega-3 fatty acids) in comparison to those from the caput (Parks & Hammerstedt 1985, Hall et al 1991, Aveldaño et al 1992, Haidl & Opper 1997, Pyttel et al 2014, Angrimani et al 2017. PUFAs possess molecular properties which increase membrane fluidity and influence transmembrane protein activities (Giroud et al 2013, Pinot et al 2014, Arnold et al 2015.…”
Section: Introductionmentioning
confidence: 99%